Fate of Bone Marrow-Derived Stromal Cells after Intraperitoneal Infusion or Implantation into Femoral Bone Defects in the Host Animal. (13th July 2010) - Wilson, Timothy; Stark, Christoffer; Holmbom, Johanna; Rosling, Ari; Kuusilehto, Asko; Tirri, Teemu; Penttinen, Risto; Ekholm, Erika
Abstract : The fate of intraperitoneally injected or implanted male rat bone marrow-derived stromal cells inside female sibling host animals was traced using Y-chromosome-sensitive PCR. When injected intraperitoneally, Y-chromosome-positive cells were found in all studied organs: heart muscle, lung, thymus, liver, spleen, kidney, skin, and femoral bone marrow with a few exceptions regardless of whether they had gone through osteogenic differentiation or not. In the implant experiments, expanded donor cells were seeded on poly(lactide-co-glycolide) scaffolds and grown under three different conditions (no additives, in osteogenic media for one or two weeks) prior to implantation into corticomedullar femoral defects. Although the impact of osteogenic in vitro cell differentiation on cell migration was more obvious in the implantation experiments than in the intraperitoneal experiments, the donor cells stay alive when injected intraperitoneally or grown in an implant and migrate inside the host. However, when the implants contained bioactive glass, no signs of Y-chromosomal DNA were observed in all studied organs including the implants indicating that the cells had been eliminated.